EDUKASI PEMAHAMAN TENTANG PEMINJAMAN SERTIFIKAT TANAH - Padma D. Liman; Birkah Latif; Dara Indrawati; Anhar Aswan; Maria Deriana Rosari Putrina Naha (The Juris, 2022)
Legal actions that simply want to hand over the right to enjoy land to other parties often turn into transfers of rights without the owner of the rights realizing it. In practice, it often happens that the owner of the right only wants to lend his land certificate to someone because the land owner knows the person and the borrower asks the land owner to help him by lending his land certificate. There are times when the borrower gives a certain amount of money to the owner of the right to want to lend the certificate. It is also common for the borrower of the certificate to explain to the owner of the certificate the reasons for borrowing the landowner's certificate. Generally, the reason for borrowing landowner certificates is to use them as collateral for credit agreements, both for credit agreements at banks and credit agreements with individuals. In such circumstances, if the owner of the right wants to help the borrower, the certificate is handed over to the borrower. In the understanding of the right owner, after a certain period of time has passed in which, they have agreed with the borrower, the borrower will return the certificate. Since the Borrower of the land certificate does not clarify the intent and purpose of borrowing the certificate to be used as collateral and if circumstances occur beyond the existence of the loan, this must be conveyed to the Owner of the certificate so that the owner of the certificate is aware of circumstances that could occur. For this reason, it is necessary to have Legal Counseling related to education on an understanding of borrowing land certificates so that it can avoid land disputes or disputes from the start.